The industrial electronics handbook - Irwin, J. David (Electrical engineering handbook series., 1997)
From traditional topics that form the core of industrial electronics to various concepts and technologies, this book presents different topics in electronics, system and process control, factory communications, measurement and instrumentation, circuits and devices, hardware, software, and factory automation.